2023
DOI: 10.1038/s41419-023-05946-2
|View full text |Cite
|
Sign up to set email alerts
|

FOXM1 is critical for the fitness recovery of chromosomally unstable cells

Abstract: Tumor progression and evolution are frequently associated with chromosomal instability (CIN). Tumor cells often express high levels of the mitotic checkpoint protein MAD2, leading to mitotic arrest and cell death. However, some tumor cells are capable of exiting mitosis and consequently increasing CIN. How cells escape the mitotic arrest induced by MAD2 and proliferate with CIN is not well understood. Here, we explored loss-of-function screens and drug sensitivity tests associated with MAD2 levels in aneuploid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 46 publications
0
11
0
Order By: Relevance
“…We were particularly interested in the transcription factor FOXM1, which has been associated with aneuploidy previously (36)(37)(38). Immunoblotting revealed that the FOXM1 expression did not increase, suggesting that rather the regulation of FOXM1 was altered after in vitro evolution (Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…We were particularly interested in the transcription factor FOXM1, which has been associated with aneuploidy previously (36)(37)(38). Immunoblotting revealed that the FOXM1 expression did not increase, suggesting that rather the regulation of FOXM1 was altered after in vitro evolution (Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Based on our observations using BCL2 overexpression in cultured cells (Figure 1; S8), we conclude that BIM may act in conjunction with other BH3-only proteins but not NOXA. Interaction with BMF 31 or BID 38 , both implicated in mitotic cell death and noted before interacting with BIM in other pathological contexts 64, 65 , deserve to be tested. Alternatively, developing T and B cell progenitors may activate alternative cell death pathways when facing mitotic delays that do not rely on BIM or any of the combinations we tested.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, tumourigenesis was accelerated by MAD2 overexpression together with MYC in blood cells or mutated KRAS in the lung epithelium 28, 29 . However, upon MAD2 overexpression, increased cell death rates were also noted, a phenomenon recently linked to FOXM1 transcription factor expression levels 31 . This may account for delayed tumour onset reported upon MAD2 overexpression in a Her2- driven mouse model of breast cancer 32 .…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…Previously, Weiler SME, et al reported that YAP could trigger aneuploid phenotype through transcriptionally activating FOXM1 expression in liver cancer 14 . However, Pan F, et al showed that FOXM1 was in reverse upregulated upon aneuploid induction in cells and facilitate mitotic exit by inhibiting the spindle assembly checkpoint 41 . Therefore, up-regulation of FOXM1 might be the result, rather than the cause, of YAP-induced aberrant mitosis.…”
Section: Discussionmentioning
confidence: 99%